Pre-Permian - Larsen, Jørgen Gutzon; Michelsen, Olaf (Danmarks Geologiske Undersøgelse Serie B, 1982)
Data on Pre-Permian rocks are reported only from the P-1 well, which was bottomed in Caledonian basement. The geology of this formation in the western part of the Danish sector is, therefore, poorly known. According to the age determinations performed and reviewed by Frost et al. (1981), the North GermanPolish Caledonides extend under most of the North Sea and join the Scottish-Norwegian Caledonides, whereas most of the Ringkøbing-Fyn High is underlain by Precambrian basement.